1990
DOI: 10.1016/s0004-9514(14)60527-4
|View full text |Cite
|
Sign up to set email alerts
|

A survey of electromodality usage in private physiotherapy practices

Abstract: This study aimed to examine ownership and usage frequencies of electrotherapeutic modalities typically found in private physiotherapy practices in Brisbane. The survey included 73 practices, representing 70 per cent of the selected sample. Results revealed that ultrasound units were used more "frequently" than any other modality. Transcutaneous electrical nerve stimulation and interferential units were also used extensively. Short-wave diathermy units were found in more clinics than any other heating modality.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
70
0
4

Year Published

1997
1997
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 10 publications
(3 reference statements)
2
70
0
4
Order By: Relevance
“…Although a high proportion of respondents to our survey had access to US (85%) and considered US use relevant to their practice (81%), the proportion who use US daily (36%) was lower than proportions reported in previous surveys (84-95%). 3,33 This is probably because our survey targeted all physical therapists in Alberta, regardless of specialization area, and therefore involved physical therapists working in areas where US may not be relevant. In fact, 78% of respondents who reported not using US also said that US was not applicable to their practice setting.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although a high proportion of respondents to our survey had access to US (85%) and considered US use relevant to their practice (81%), the proportion who use US daily (36%) was lower than proportions reported in previous surveys (84-95%). 3,33 This is probably because our survey targeted all physical therapists in Alberta, regardless of specialization area, and therefore involved physical therapists working in areas where US may not be relevant. In fact, 78% of respondents who reported not using US also said that US was not applicable to their practice setting.…”
Section: Discussionmentioning
confidence: 99%
“…Factors that may be contributing to this decreased use of US are unconvincing evidence for its effectiveness (35% of our respondents reported that US was not effective in their clinical experience and that they prefer other modalities to accomplish therapeutic objectives) and a lower rate of access to US equipment (81%) relative to that reported in other surveys (99%). 3,33 General use of US for therapeutic purposes…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations